2009
DOI: 10.1155/2009/510124
|View full text |Cite
|
Sign up to set email alerts
|

A novel Multiple-Marker Method for the Early Diagnosis of Oral Squamous Cell Carcinoma

Abstract: Abstract. Objective: Melanoma associated antigens-A (MAGE-A) expression is highly specific to cancer cells. Thus, they can be the most suitable targets for the diagnosis of malignancy. The aim of this study was to evaluate the sensitivity of multiple MAGE-A expression analysis for the diagnosis of oral squamous cell carcinoma (OSCC). Methods: Total of 70 OSSC and 20 normal oral mucosal (NOM) samples of otherwise healthy volunteers were examined for the expression of 10 different single antigens out of 12 diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…In the literature, correlations among binary markers are often not described directly but may be inferred. For example, Ries et al examined 12 MAGE-A antigens for oral squamous cell carcinoma (OSSC) 8. They reported that singly, six of these markers were positive at rates between 40% and 55% for OSSC; each was negative in all control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, correlations among binary markers are often not described directly but may be inferred. For example, Ries et al examined 12 MAGE-A antigens for oral squamous cell carcinoma (OSSC) 8. They reported that singly, six of these markers were positive at rates between 40% and 55% for OSSC; each was negative in all control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the tissue analysis of suspected lesions, the molecular diagnosis of early oral cancer has recently developed. Expression of MAGE-A was restricted to OCSCC and was considered to be used in the early detection of oral cancer [144]. The epithelial tumor markers Cyfra 21-1, TPS and CA12, various oxidative stress-related salivary parameters, such as reactive oxygen species and reactive nitrogen species, biochemical and immunological para meters, such as IGF, MMPs and RNA transcripts of IL8, IL-1B, DUSP1, HA3, OAZ1, S100P and SAT were altered significantly in the saliva, an observation that is potentially useful in the early detection of oral cancer in the future [145].…”
Section: Current Molecular Markers Applied To Early Diagnosis Of Ocsccmentioning
confidence: 99%
“…Expression of human melanoma‐associated antigen ( MAGE ) family genes has been recently associated with several types of cancer 3–7. The first human MAGE family member was discovered as a gene encoding a tumor‐specific antigen 8.…”
mentioning
confidence: 99%